Establishment and external validation of neutrophil-to-lymphocyte ratio in excluding postoperative pancreatic fistula after pancreatoduodenectomy. Issue 1 (12th January 2023) - Garnier, Jonathan; Alfano, Marie-Sophie; Robin, Fabien; Ewald, Jacques; Al Farai, Abdallah; Palen, Anais; Sebai, Amine; Mokart, Djamel; Delpero, Jean-Robert; Sulpice, Laurent; Zemmour, Christophe; Turrini, Olivier
Abstract: Background: Factors excluding postoperative pancreatic fistula (POPF), facilitating early drain removal and hospital discharge represent a novel approach in patients undergoing enhanced recovery after pancreatic surgery. This study aimed to establish the relevance of neutrophil-to-lymphocyte ratio (NLR) in excluding POPF after pancreatoduodenectomy (PD). Methods: A prospectively maintained database of patients who underwent PD at two high-volume centres was used. Patients were divided into three cohorts (training, internal, and external validation). The primary endpoints of this study were accuracy, optimal timing, and cutoff values of NLR for excluding POPF after PD. Results: From 2012 to 2020, in a 2:1 ratio, 451 consecutive patients were randomly sampled as training ( n = 301) and validation ( n = 150) cohorts. Additionally, the external validation cohort included 197 patients between 2018 and 2020. POPF was diagnosed in 135 (20.8 per cent) patients. The 90-day mortality rate was 4.1 per cent. NLR less than 8.5 on postoperative day 3 (OR, 95 per cent c.i.) was significantly associated with the absence of POPF in the training (2.41, 1.19 to 4.88; P = 0.015), internal validation (5.59, 2.02 to 15.43; P = 0.001), and external validation (5.13, 1.67 to 15.76; P = 0.004) cohorts when adjusted for relevant clinical factors. Postoperative outcomes significantly differed using this threshold. Conclusion: NLR less than 8.5 on postoperative day 3 may be a simple, independent, cost-effective, and easy-to-use criterion for excluding POPF. Abstract : Neutrophile to lymphocyte ratio less than 8.5 on postoperative day 3 may be a simple, independent, and cost-effective criterion for excluding postoperative pancreatic fistula after pancreatoduodenectomy.